Study And Design Of Optical Single Sideband Subcarrier Multiplexing Using QPSK Modulation - Lee, Ruen Chung (2005)
Wavelength division multiplexing (WDM) optical systems are subjected to high costs and instability of the optical components reguired for implementation. The advantages and potential of intensity modulated direct detection systems to overcome these issues can be exploredand realized. Subcarrier Multiplexing (SCM) can be used to subdivide the available RF bandwidth in a single wavelength system.